False Rosemary, Conradina canescens - Debbie Miller; Mack Thetford; Chris Verlinde; Gabriel Campbell; Ashlynn Smith (EDIS)
False rosemary is found on the backsides of foredunes, on all sides of backdunes, and inland in scrub communities. False rosemary is killed by fires but will reseed to an area in the absence of further disturbance. It is endemic to west Florida and Alabama, contributes to beach mouse habitat, and attracts many pollinators. https://edis.ifas.ufl.edu/sg167